2013
DOI: 10.3178/hrl.7.36
|View full text |Cite
|
Sign up to set email alerts
|

Future projection of mean river discharge climatology for the Chao Phraya River basin

Abstract: Abstract:We projected future river discharge in the Chao Phraya River basin and evaluated the uncertainty in future climate projections by using different resolutions and ensemble experiments of the Atmospheric General Circulation Model of the Meteorological Research Institute (MRI-AGCM). We also obtained estimates of precipitation, evaporation, runoff, and river discharge under climate conditions projected for the late 21st century. The results show that precipitation is projected to significantly increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
(21 reference statements)
0
11
2
1
Order By: Relevance
“…However, Kure and Tebakari (2012) and this study projected large increases in runoff under the late future climate. Champathong et al (2013) projected a significant increase in evapotranspiration in the entire basin, which differs from our results. Champathong et al (2013) indicated that a projected increase in precipitation was not significant in the Ping and Wang River basins, suggesting that fewer cloudy days were projected by their GCMs than by the CMIP5 AOGCMs.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…However, Kure and Tebakari (2012) and this study projected large increases in runoff under the late future climate. Champathong et al (2013) projected a significant increase in evapotranspiration in the entire basin, which differs from our results. Champathong et al (2013) indicated that a projected increase in precipitation was not significant in the Ping and Wang River basins, suggesting that fewer cloudy days were projected by their GCMs than by the CMIP5 AOGCMs.…”
Section: Discussioncontrasting
confidence: 57%
“…Champathong et al (2013) projected a significant increase in evapotranspiration in the entire basin, which differs from our results. Champathong et al (2013) indicated that a projected increase in precipitation was not significant in the Ping and Wang River basins, suggesting that fewer cloudy days were projected by their GCMs than by the CMIP5 AOGCMs. That could also explain the increase in evapotranspiration projected by Champathog et al (2013).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations